2021
DOI: 10.1108/bfj-03-2021-0341
|View full text |Cite
|
Sign up to set email alerts
|

Fostering ethical consumption in food sector: Insights from the Italian Solidarity Purchasing Groups

Abstract: PurposeThe paper aims at investigating antecedents and predictors of consumers' buying and consumption processes within the Italian Solidarity Purchasing Groups (SPGs) to enrich current debate about drivers and levers on which act for fostering ethical consumption in food sector.Design/methodology/approachBuilding upon the theory of planned behavior (TPB) a theoretical model is proposed for depicting possible antecedents and predictors of consumers' buying and consumption processes in food sector. The validity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…Subjective norm refers to the perceived social pressure or expectation to engage or not engage in a particular behavior (Sciarelli et al, 2021;Shurrab et al, 2019;Obrenovic et al, 2022). It is a crucial component of the TRA, developed by Fishbein and Ajzen (1975).…”
Section: Subjective Normmentioning
confidence: 99%
See 2 more Smart Citations
“…Subjective norm refers to the perceived social pressure or expectation to engage or not engage in a particular behavior (Sciarelli et al, 2021;Shurrab et al, 2019;Obrenovic et al, 2022). It is a crucial component of the TRA, developed by Fishbein and Ajzen (1975).…”
Section: Subjective Normmentioning
confidence: 99%
“…For example, in some cultures, it may be considered inappropriate to watch certain types of content, while in others, it may be encouraged. Furthermore, research has shown that subjective norms can also influence people's actual behavior (Aksoy and Abdulfatai, 2019;Wu et al, 2022;Sciarelli et al, 2021). In regard to the context of video published on YouTube, when individuals perceive that their friends, family or social media connections approve of or engage in watching certain videos, their own behavior is likely to be influenced.…”
Section: Intention and Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the traditional approach of the role of consumers in the agri-food systems, several concepts and initiatives have been developed considering a more active role for both individual and collective consumers/citizens in the agri-food value chain. For instance, sustainable consumption has emerged in marketing scholarship as a pressing matter [67,69], followed by other initiatives, such as ethical consumption [70], responsible consumer behavior [71], reflexive consumption [72], green procurement/consumption [73] and green certification [74]. However, these initiatives have also narrowed the focus only on the consumption part of the agri-food value chain and the proposed solutions have focused on merely consumers rather than a systemic alternative that encompasses a broader context involving other stages of the value or supply chain.…”
Section: Inputs Farming Processing/ Distribution Retailers Consumersmentioning
confidence: 99%
“…Self-organized citizen groups (as introduced in Section 3.1) are social innovations that capture self-management and self-mobilization in supplying agri-food products. "Collective food buying groups", such as "solidarity purchasing groups" (SPG), are examples of business models which are formed for the aim of supplying food based on the mutual values and needs of the local collective citizens [70]. Solidarity purchasing groups are defined as groups of households that establish mutual coordination for the purpose of purchasing food directly from sustainable producers, who are selected in accordance with ethical and solidarity principles such as environment and social values [125] (p. 232).…”
Section: Connecting Consumers/citizens To Growers and Nature Through Innovative Business Modelsmentioning
confidence: 99%